Evidence laid before the Congo Commission of Inquiry at Bwembu, Bolobo, Lulanga, Baringa, Bongandanga, Ikau, Bonginda, and Monsembe. - Congo Commission of Inquiry (Liverpool : Richardson & Sons, 1905)
Bibliotheek E. Anseele
Together with a Summary of Events on the A.B.I.R. Concession
Engels
Brochure